KOMPOSISI SERANGGA MALAM YANG DITEMUKAN DI AREAL KEBUN BUAH NAGA BERDAGING MERAH DI KENAGARIAN IV KOTO HILIE KECAMATAN BATANG KAPASKABUPATEN PESISIR SELATAN - Satria, Wiwit; Nurhadi, Nurhadi; safitri, Elza (STKIP PGRI Sumbar, 2014)
ABSTRACT Insects are animals that live in any places which is live in the sea , on land and in the air . One of them is live around the plants , insects act as pollinators , decomposers and also as a pest , an insect has very important meaning in human life , as insects visiting flowers to take liquid food such as sweet . Based on the fact above, the composition of the research has been done in the night insects which visiting the plants in dragon fruit in Kenagarian IV Koto Hilie Kecamatan Batang Kapas Kabupaten Pesisir Selatan.This study is used a descriptive survey method is by direct collection of insects evening of the research sites with Light Trap. Sampling is done on two stations : Station I in dragon fruit plants by using 2 traps , and there disemak station II by using the I trap .The composition of night insects found in the garden area in the red dragon fruit in Kenagarian IV Koto Hilie Kecamatan Batang Kapas kabupaten Pesisir Selatan consists of 6 Ordo , 6 , 11 Family nd 13 Genus . The highest relative of density is Symphomyia genus that is ( 41.28 % ) and the lowest relative density is the Aedes genus ( 0.92 % ) .